Researching a sensitive topic in an unstable environment: Fieldwork dilemmas in the Khyber-Pakhtunkhwa province of Pakistan. (24th July 2019) - Saeed, Muhammad; Griffin, Gabriele
Abstract : Purpose: The purpose of this paper is to explore fieldwork dilemmas for a Pakhtun researcher, educated in the West, to research family or domestic violence in the unstable, hostile environment of the Khyber-Pakhtunkhwa province, Pakistan. Design/methodology/approach: A gender studies approach is here combined with masculinities studies, and a critical qualitative research methodology is used in this study. Findings: The paper argues that unstable regions dominated by certain forms of masculinity require specific research approaches when conducting research and addressing a topic that is culturally taboo. Practical implications: The paper suggests how the insider–outsider dynamic plays out for researchers who come from a particular field and return to it under changed circumstances. It also indicates how a taboo topic in a context where direct questioning is not possible might be approached through the use of vignettes. Social implications: The paper suggests how the contradictory position of a masculinity, simultaneously bearing traces of the hegemonic and of marginalization, may be negotiated in the field. Originality/value: Social research on the Khyber-Pakhtunkhwa province of Pakistan is rarely conducted and reported due to the unrest in this region. The paper thus contributes original insights from fieldwork carried out there. It also contributes to the limited but growing literature on conducting fieldwork in hostile environments.